PENGARUH KOMPETENSI, KOMPENSASI DAN PENGEMBANGAN KARIR TERHADAP KINERJA PEGAWAI PADA DINAS KESEHATAN KOTA BAUBAU PROVINSI SULAWESI TENGGARA - Herman , Ari; Adriansyah , Ahmad (Journal of Accounting, Management and Islamic Economics, 2025)
Human resources for health (HR) is one of the sub-systems in the national health system that has an important role in providing quality services to the community, even though the adequacy of resources alone is not enough to ensure that an activity or program can run well. appropriate to place individuals in carrying out certain tasks according to their abilities and of course educational qualifications. This study aims to examine and analyze the effect of competence, compensation, and career development on employee performance in a positive and significant way. The research method used is a non-experimental analytic survey and Structural Equation Modeling (SEM) data analysis techniques and data processing using AMOS 20. The results showed that 3 variables which include competence, compensation, and career development proved to have a positive effect on employee performance. And the results of competency reliability tests and career development have the greatest influence on employee performance. And compensation variable is not so big influence on employee performance.